2021
DOI: 10.1186/s13071-021-04619-3
|View full text |Cite
|
Sign up to set email alerts
|

A long-lasting emerging epidemic of anthroponotic cutaneous leishmaniasis in southeastern Iran: population movement and peri-urban settlements as a major risk factor

Abstract: Background Epidemics of cutaneous leishmaniasis (CL) are occurring more frequently and spreading faster and farther than before in many areas of the world. The present study aimed to assess a long-lasting emerging epidemic (2005–2019) of 5532 cases with anthroponotic CL (ACL) in peri-urban areas of Kerman city in southeastern Iran. Methods This descriptive-analytical study was carried out for 15 years in Kerman province, southeastern Iran. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
(51 reference statements)
1
23
0
1
Order By: Relevance
“…The findings of this study demonstrated that the main causative agent of ZCL cases in the 14 provinces is L. major and the main causative agent of ACL cases in the five provinces is L. tropica (Figure 2). Although L. tropica was formerly common in many large urban areas, it has also been observed in rural areas and small cities in Iran (169). According to the findings of the two studies, four isolates of L. turanica were found in CL patients in the Gonbad-Kavous and Turkmen Sahara districts of Golestan province, which are the known oldest ZCL foci (90,121).…”
Section: Discussionmentioning
confidence: 97%
“…The findings of this study demonstrated that the main causative agent of ZCL cases in the 14 provinces is L. major and the main causative agent of ACL cases in the five provinces is L. tropica (Figure 2). Although L. tropica was formerly common in many large urban areas, it has also been observed in rural areas and small cities in Iran (169). According to the findings of the two studies, four isolates of L. turanica were found in CL patients in the Gonbad-Kavous and Turkmen Sahara districts of Golestan province, which are the known oldest ZCL foci (90,121).…”
Section: Discussionmentioning
confidence: 97%
“…The disease affects a number of the poorest people in the world and is linked with population movement, poor housing conditions, deficient immune systems, and lack of monetary resources. Rural-urban labor migration, civil unrest, and climate change remain significant additional risk factors for ACL (Desjeux, 2001;Karimi et al, 2021). Leishmaniasis is also related to environmental modifications, including deforestation, dam building, urbanization, and irrigation schemes (WHO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in table (5), the domestic and pets animals found in and around the houses, dogs found in four houses, all the people found in these houses were positive, three houses having cats and dogs two were positive and one negative. The result showed there was a significant difference between them (P-value = 0.013).…”
Section: Results Of Leishmanin Skin Test (Montenegro Skin Test)mentioning
confidence: 93%
“…Cutaneous Leishmaniasis (CL) is a common health problem in the world, it is divided into Zoonotic Cutaneous Leishmaniasis (ZCL) and Anthroponotic Cutaneous Leishmaniasis (ACL) [5]. ZCL was reported in Sudan and has been considered to be the second parasitic health problem after malaria.…”
Section: Introductionmentioning
confidence: 99%